2022
DOI: 10.3390/biomedicines10030663
|View full text |Cite
|
Sign up to set email alerts
|

Impact of miR-1/miR-133 Clustered miRNAs: PFN2 Facilitates Malignant Phenotypes in Head and Neck Squamous Cell Carcinoma

Abstract: Based on our original RNA sequence-based microRNA (miRNA) signatures of head and neck squamous cell carcinoma (HNSCC), it was revealed that the expression levels of miR-1-3p, miR-206, miR-133a-3p, and miR-133b were significantly suppressed in cancer specimens. Seed sequences of miR-1-3p/miR-206 and miR-133a-3p/miR-133b are identical. Interestingly, miR-1-3p/miR-133a-3p and miR-206/miR-133b are clustered in the human genome. We hypothesized that the genes coordinately controlled by these miRNAs are closely invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…Overexpression of PFN2 was reported in several types of cancers, including HNSCC [ 42 ]. Recently, we revealed that PFN2 was directly regulated by tumor-suppressive miR-1 / miR-133 clustered miRNAs in HNSCC cells, and its overexpression promoted cancer cell malignant transformation [ 25 ]. Another study showed that overexpression of PFN2 enhanced the aggressiveness of small cell lung cancer (SCLC), including cell proliferation, migration, and invasion.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Overexpression of PFN2 was reported in several types of cancers, including HNSCC [ 42 ]. Recently, we revealed that PFN2 was directly regulated by tumor-suppressive miR-1 / miR-133 clustered miRNAs in HNSCC cells, and its overexpression promoted cancer cell malignant transformation [ 25 ]. Another study showed that overexpression of PFN2 enhanced the aggressiveness of small cell lung cancer (SCLC), including cell proliferation, migration, and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…The protocols used for transient transfection of miRNAs and siRNAs were described in our previous studies [ 23 , 24 , 25 , 26 ]. The miRNA precursors and siRNAs used in this report were detailed in Table S2 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations